Surveillance des effets de la pollution atmosphérique en milieu urbain sur la santé : le Programme français PSAS-9 - Sylvie Cassadou; Christophe Declercq; Daniel Eilstein; Pascal Fabre; Laurent Filleul; Alain Le Tertre; Agnès Lefranc; Sylvia Medina; Catherine Nunes; Laurence Pascal; Hélène Prouvost; Abdelkrim Zeghnoun (VertigO)
Title : Health Impact assessment of urban air pollution : results from nine French cities and their utility for public health management.The epidemiological surveillance program in 9 French cities (PSAS-9) aims to estimate the relationships between air pollution and health risks in order to assess the impact of the urban air pollution on health. Trough a standardized protocol, the 9 French cities collected daily aggregated data on air pollution trough a metrology measure network and mortality data from official registers. These data were modelized according to the time series analysis method. Depending on the pollutant, excess in total mortality risk related to a 10 µg/m3 pollutant increase varied between 1.2 and 1.9%. If the average level of the pollutant was reduced by 50 %, the total account of attributable deaths would be of 2786 per year in the 9 cities.